Functionality based method for simultaneous isolation of rodent hepatic sinusoidal cells. (September 2017) - Stradiot, L.; Verhulst, S.; Roosens, T.; Øie, C.I.; Moya, I.M.; Halder, G.; Mannaerts, I.; van Grunsven, L.A.
Abstract: Chronic liver disease is the result of long term exposure to viruses or toxins such as alcohol, fat and drugs, and forms the basis for the development of liver fibrosis and primary liver cancer. In vitro and in vivo models are key to study the pathways involved in chronic liver disease and for the development of therapeutics. 3D co-culture systems are becoming the in vitro standard, which requires freshly isolated primary hepatic cells. We developed a novel isolation method to simultaneously isolate liver sinusoidal endothelial cells (LSECs), Kupffer cells (KCs) and hepatic stellate cells (HSCs). The method exploits the scavenging activity of LSECs, the phagocytic capacity of KCs and the retinoid content of HSCs in vivo to enable direct processing by fluorescence-activated cell sorting without additional antibody binding and washing steps. UFACS3, for UV-FACS-based isolation of 3 non-parenchymal liver cell types, yields functional and pure LSECs (98 ± 1%), KCs (98 ± 1%) and HSCs (97 ± 3%), with less hands-on time from healthy and diseased rodent livers. This novel approach allows a fast and effective combined isolation of sinusoidal cells for further analysis.